Clinical education of BSC OT students by clinical occupational therapists: a mixed methods study - De Witt, Patricia Ann (My University, 2016)
Part 1: Factors influencing the quality of clinical education for occupational therapy students. A qualitative study revealed that despite pockets of excellent clinical education there were quality issues. Factors affecting quality: lack of clinical education knowledge; time pressures; poor role-modelling; inconsistent student assessment; coping skills; attitudes to learning and the clinical curriculum. Quantitative studies illustrated that undergraduate courses provide little knowledge and skill that prepare graduates for future roles as clinical educators. Departmental managers provide limited support and little educational leadership. The academic department provides support and procedural training but this is insufficient. Training was recommended. Part 2: Examination of training of clinical educators to improve quality. An integrative literature review was used to develop a clinical educator skill-set. A survey was used to collect clinical educators’ rating of their knowledge, skill and attitude to clinical education. Results showed a gap in knowledge and skill and a significant difference between experienced and inexperienced clinical educators. Practical action research was used to design and develop a training programme for inexperienced clinical educators. A quasi-experimental pilot study tested the value and outcome of the training. Before and after training scores of 22 participants were significantly different, but training failed to demonstrate any improvement in quality from the students’ experience. Methodological problems in data collection may have influenced the results. Conclusion: Current clinical education lacks administrative and pedagogic consistency which is not ameliorated by a single intervention for inexperienced clinical educators. A model for additional training is proposed.
A thesis submitted to the Faculty of Health Sciences, University of Witwatersrand, in fulfilment of the requirements of the degree of Doctor of Philosophy. Johannesburg, 2016